P331 Clinical and electroencephalography role in prediction of outcome in survivors after cardiopulmonary resuscitation. Issue 9 (September 2017) - Hosny, Hanan; Nada, Mona; Shaker, Ehab; Nawito, Amani; Seleem, Mohamed; Hassan, Rehab; Nafia, Hesham
Abstract : Objective: To outline the reliable predictors of both favorable and unfavorable outcomes of anoxic-ischemic encephalopathy. Subjects: Forty patients from National Heart Institute Hospital who regained spontaneous circulation after cardiac arrest classified into 2 groups according to outcome, group A (favorable outcome), and group B (unfavorable outcome). Methods: All patients were subjected to digital EEG, QEEG and clinical assessment at Day 1, 3 and 7 from restoration of spontaneous circulation. The results were compared, and correlated with neurological outcome. Results: The mean of age was 54.6 ± 11.9 years (range, 26–70 years). Eighteen patients (45%) were discharged after recovery and twenty-two patients (55%) died in CCU. The survivred patients had relatively shorter CPR time 9.4 ± 7.8 min, compared to the dead patients16.6 ± 10.6 min. Alteration in the mental state was significantly higher in patient with poor outcome within Day 3 compared to patients with good outcome, ( P  = 0.000). Failure to regain brainstem reflexes after 72 h was a significant predictor of poor outcome, ( P  = 0.003). Failure to have EEG background reactivity in Day 1 or regain it in Day 3 was a significant predictor of poor outcome, ( P  = 0.004, 0.003 respectively). The sensitivity and specificity for poor outcome for amplitude of O1 higher than 2.7 was 63.3% and 44.4% respectively, O2 higher than 2.4 was 68.2% and 44.4% respectively and Cz higher than 1.5 was 68.2% 50% respectively. In conclusion: The correlation between EEG data and global functional outcome are possibly confident within 72 h.